PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDI BERTINGKAT KELAPA LIMA 2 - Nahak, Arniyanti Hoar; Ga, Paulina Riwu; Kota, Martha K (Journal of Character and ELementary Education, 2024)
This research aims to improve student learning outcomes through the application of the Problem Based Learning learning model in class V SDI Level Kelapa Lima 2. The learning model for this research is classroom action research with data collection techniques namely Observation, Tests, and Documentation. The research results showed that in the first cycle, 9 of the 21 students completed (42.83%) with an average score of 65.71. Meanwhile, 12 people (57.17%) did not complete it. Furthermore, in Cycle II student learning outcomes experienced an increase, namely from 21 students who completed 18 (82.60%) with an average score of 81.42 because students were more active and directly involved in activities in class during the learning process, students worked together in solving problems quickly, students are able to take responsibility in group work and students are more active in participating in learning. Based on the research results, it can be concluded that through the application of the Problem-Based Learning Model to improve the Learning Outcomes of Class V SDI Level 2 Kelapa Lima 2 Students, it can improve student Learning Outcomes and meet the minimum Completeness Criteria Expected by the Researcher